DESIGN HOUSE RENTAL STORES COMPUTERIZED SYSTEM (SHOP) IN PT. XYZ - Ade Syayuddin; Aqwam Rosadi Kardian SKom, MM (Jurnal Sistem Informasi, 1999)
PT. RAY NOBLE ENDOWMENT is a new company engaged in the sale and rentalof shop houses (shop). The company has a weakness in its business that is giveinformation to consumers, recording, storage is still using the big book or manual.Because of that, in this writing, the author tries to make the computerized dataprocessing systems primarily provide information on the process of shop houses,listing tenants and transaction data with the tool. With the development of systemsand system design is done, the writer tries to create a computerized system forprocessing of administrative data that form the core of the discussion in this writing.